Axial position estimation of conical shaped motor for green taxiing application - Roggia, S.; Galea, Michael; Gerada, C.; Cupertino, Francesco (2017)
This paper considers the possibility of adopting a conical shaped motor for Green Taxiing (GT) application. This topology of motor has been selected in order to obviate the presence of external declutching system (i.e. mechanical or electromagnetic clutch) interposed between the electric actuator and the wheel. An axial force contributes to move the rotor inside-out of the stator (principle of sliding-rotor). The axial movement of the rotor can be monitored acting on the magnetizing current. The axial sensor-less position estimation method described hereafter envisages the possibility of evaluating the axial position of the rotor during the engaging and disengaging movement from the wheel. The axial position calculation is dependent on the inductance of the motor. An “on¬line” computation of the position has been implemented through the use of high-frequency injection signals.